2020
DOI: 10.1093/cercor/bhaa312
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Brain Oscillations: High Arousal is Associated with Decreases in Alpha- and Lower Beta-Band Power

Abstract: The study of brain oscillations associated with emotional picture processing has revealed conflicting findings. Although many studies observed a decrease in power in the alpha- and lower beta band, some studies observed an increase. Accordingly, the main aim of the present research series was to further elucidate whether emotional stimulus processing is related to an increase or decrease in alpha/beta power. In Study 1, participants (N = 16) viewed briefly presented (150 ms) high-arousing erotic and low-arousi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 44 publications
10
51
0
Order By: Relevance
“…Considering the active inhibitory role of alpha enhancement as well as OFC regulatory role, we suggest that the late OFC alpha-beta power enhancement detected in the current empathy study reflects a top-down inhibitory control mechanism in perceiving painful stimuli to regulate emotion and social behavior. Our findings are partially in line with a recent article examining three different EEG studies on negative and positive high arousal emotions (first study: erotic vs neutral; second study: mutilation vs neutral; third study: erotic vs mutilation; Schubring and Schupp, 2021). Schubring and Schupp reported an early alpha/low-beta (10-16 Hz) suppression in response to observing mutilation pictures over the central sensors, showing activation at the sensory area as well as a late alpha/low-beta (10-20 Hz) enhancement over anterior and posterior EEG sensors in response to observing negative but not positive high arousal stimuli, representing functional inhibitions to negative stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Considering the active inhibitory role of alpha enhancement as well as OFC regulatory role, we suggest that the late OFC alpha-beta power enhancement detected in the current empathy study reflects a top-down inhibitory control mechanism in perceiving painful stimuli to regulate emotion and social behavior. Our findings are partially in line with a recent article examining three different EEG studies on negative and positive high arousal emotions (first study: erotic vs neutral; second study: mutilation vs neutral; third study: erotic vs mutilation; Schubring and Schupp, 2021). Schubring and Schupp reported an early alpha/low-beta (10-16 Hz) suppression in response to observing mutilation pictures over the central sensors, showing activation at the sensory area as well as a late alpha/low-beta (10-20 Hz) enhancement over anterior and posterior EEG sensors in response to observing negative but not positive high arousal stimuli, representing functional inhibitions to negative stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…Thus far, the studies that looked into neural rhythms underlying empathy mainly reported the involvement of the alpha rhythm ( Perry et al, 2010 ; Whitmarsh et al, 2011 ; Woodruff et al, 2011 ; Chen et al, 2012 ; Hoenen et al, 2015 ; Motoyama et al, 2017 ; Rieèanskı and Lamm, 2019 ). Alpha-band activity is involved in numerous emotional and cognitive processes ( Klimesch et al, 2007 ; Hanslmayr et al, 2012 ; Bauer et al, 2014 ; Frey et al, 2015 ; Sadaghiani and Kleinschmidt, 2016 ; Schubring and Schupp, 2021 ), and in particular, it has a unique dual functionality: a cortical inhibitory control role reflected by an increase in alpha band power (i.e., enhancement) as well as an active role “gating by inhibition” ( Jensen and Mazaheri, 2010 ). Accordingly, alpha power suppression is thought to reflect release from inhibition in the brain ( Pfurtscheller and Lopes da Silva, 1999 ; Mazaheri et al, 2009 ; Haegens et al, 2010 ; Jensen and Mazaheri, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ey found that when the subjects faced lower quality synthetic text, the neuron activity in the alpha band of the left frontal lobe increased [31]. However, Schubring et al found that when subjects dealt with high arousal emotional stimuli, the energy in the alpha band decreased [32]. In short, energy changes in the alpha band are closely related to emotional stimulation processing.…”
Section: E Analysis Of Functional Network Connectionmentioning
confidence: 98%